Amyloidosis – short review (Journal of Medical Science, 2016)
Amyloidosis is a heterogeneous group of disorders associated with pathological deposition of amyloid. We can recognize two major categories of amyloidosis: primary (AL) and secondary (AA) type. Systemic monoclonal immunoglobulin light-chain (AL) is the most common form of systemic amyloidosis. Systemic AA amyloidosis is associated with chronic inflammation or infective diseases and is the second common form of systemic amyloidosis. The golden standard in diagnosis of amyloidosis is biopsy. The model of treatment depends of type of amyloidosis. In some cases there is considerate cell transplantation. In AA the purpose is to decrease inflammation.